2022
DOI: 10.3389/fmed.2022.953084
|View full text |Cite
|
Sign up to set email alerts
|

Profile of coronavirus disease enlightened asthma as a protective factor against death: An epidemiology study from Brazil during the pandemic

Abstract: IntroductionThe possibility that asthma is not a risk factor for the worst outcomes due to coronavirus disease (COVID-19) is encouraged. The increase in Th2 response dominance can downregulate the late phase of hyperinflammation, which is typically the hallmark of more severe respiratory viral infections, alongside lower angiotensin-converting enzyme receptors in patients with asthma due to chronic inflammation. Few studies associated asthma diagnosis and COVID-19 outcomes. In this context, we aimed to associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 77 publications
0
0
0
1
Order By: Relevance
“…Even, in the literature, some studies demonstrated only a higher prevalence of COVID-19 among patients with BD without impact on severity [10,27,31]. Moreover, it is important to highlight the need for a correct diagnosis even among those with a rare COVID-19 phenotype [35,36,45]. In brief, in Brazil, Boschiero et al ( 2022) evaluated a population of 1,851,592 hospitalized individuals due to COVID-19 with the data for COVID-19 and outcomes, among these individuals, 632,101/ (34.1%) deaths were observed [41].…”
Section: Discussionmentioning
confidence: 99%
“…Even, in the literature, some studies demonstrated only a higher prevalence of COVID-19 among patients with BD without impact on severity [10,27,31]. Moreover, it is important to highlight the need for a correct diagnosis even among those with a rare COVID-19 phenotype [35,36,45]. In brief, in Brazil, Boschiero et al ( 2022) evaluated a population of 1,851,592 hospitalized individuals due to COVID-19 with the data for COVID-19 and outcomes, among these individuals, 632,101/ (34.1%) deaths were observed [41].…”
Section: Discussionmentioning
confidence: 99%
“…Um estudo brasileiro com as primeiras 250.000 internações por COVID-19 apontou a predominância do sexo masculino em 56%, presença de comorbidades em 84%, mortalidade hospitalar de 38%, sendo que 59% dos pacientes estavam na UTI (forma grave) e 80% dos óbitos foram em pacientes ventilados mecanicamente 21…”
Section: Discussionunclassified
“…Apesar do senso comum indicar que toda doença respiratória enquadraria o paciente no grupo de risco máximo de Covid-19, os resultados estatísticos obtidos vão ao encontro com a pesquisa de Sansone et al (2022), que classificou a asma como uma condição de fator protetor a essa doença. Para investigação dos resultados, expõe-se que o coeficiente dos pacientes com pré-existência de doença hepática é de 0,4538, com IC de 95% entre 0,4562 e 0,4515, e razão de chances de 1,5743, indicando que estes pacientes possuem significativamente mais chances de vir a óbito por Covid-19 quando comparados aos enfermos que não apresentam essa préexistência em seu quadro clínico.…”
Section: Relação Das Condições E Doençasunclassified